Intertap interval dependence of the subdivision effect in auditory‐synchronised tapping. (22nd November 2021) - Ono, Kentaro; Hashimoto, Junya; Sasaoka, Takafumi
Abstract: Precise temporal synchronisation between action and perception is crucial in daily life. Interestingly, synchronised tapping for every other tone or more (1: n tapping) is more precise than that for each tone (1:1 tapping), and this phenomenon is called 'subdivision benefit'. One hypothesis to explain this phenomenon is that there is a tendency to underestimate an empty interval, but the subdivision is used as an additional temporal reference and causes an illusionary longer intertap interval (ITI). The other hypothesis is based on strong/weak beats in a tone sequence made by subdivision. Because the strong beat improves the sensitivity of duration perception, synchronisation with strong beats should be better compared with other beats. Instead, the first hypothesis suggests that the subdivision benefit occurs irrespective of beat strength. The present study aimed to clarify this discrepancy using a 1:3 tapping task for a sequence of three‐tone patterns and a 1:1 tapping task for a sequence of a single tone repetition. A further aim was to clarify the effect of musical experience. When the ITI was 900 ms or more, the variability of tapping showed the subdivision benefit, irrespective of beat strength. This result supports the first hypothesis, and musicians obtained more benefits than non‐musicians. Instead, the timing of tap did not shorten by subdivision, except for the ITI of 900 ms. The findings implicate that the subdivision benefit is due to the additional temporal reference by the subdivided tones, and the benefit is dependent on the ITI length. Abstract : We conducted a behavioural experiment to investigate the psychological mechanisms of sensory–motor synchronisation by introducing a rhythmic structure using a subdivision in a tone sequence. Subdivided tones made synchronised tapping less variable than a simple repetition of a tone when the intertap interval was 900 ms or more. On the other hand, a shorter intertap interval of 600 ms caused synchronisation more variable.